Paz, guerra e intervenção no pensamento de Kant : possibilidades e limites do uso da força no direito internacional - Brasil, Luciano de Faria (2019)
The thesis examines Kant’s thought on war, analyzing its potential admissibility, its boundaries and its function in Kant’s juridical and political theory. The text analyzes the texts of “Toward Perpetual Peace” and “Doctrine of Right” to better comprehend Kant’s thought on public law, international law and cosmopolitan law. There is an explanation on the essential parts of public law: the idea of a juridical state, the notion of original contract and the idea of republican constitution. The text also analyzes the divergences between the texts of “Toward Perpetual Peace” and “Doctrine of Right”, with a proposal of an explanation based in the view of selected authors. According to the thesis, Kant disapproves morally the war, but admits its existence in the state of nature between the nations, under a provisional international law, in specific cases and with limited means. Kant admits self-defense to protect the safety of the State, also in a precautionary basis. In the hypothesis of existence of an unjust enemy, the function of war in Kant’s thought becomes clearer. There is a permission to enforce the removal of the unjust enemy from the state of nature between States, and to enforce the establishment of a new constitution, increasing the number of republics eligible to enter in a juridical state between nations. In this view, the war connects with the essential parts of public law according to Kant’s thought, and must serve to promote the juridical state and the republican constitution. Although morally negative, the war can serve, as a last resource, as a means to achieve perpetual peace.